Effectiveness of Menstrual Hygiene Management Education on Knowledge of Young Women - Fira Amalia Hanifah; Masrina Munawarah Tampubolon; Jumaini Jumaini (CV. Rayyan Dwi Bharata, 2024)
Background: Low knowledge about reproductive health will allow adolescent girls to be minimal in maintaining cleanliness during menstruation. One of the activities carried out to increase the knowledge of young women is to provide health education about menstrual hygiene management (MHM). Method: This study used quantitative design with quasi-experimental method and one group pretest-posttest design research design. The sample of this study was 50 grade VII junior high school students taken using cluster random sampling technique. The analysis used used the Wilcoxon statistical test. Results: After being given education about MHM with the lecture method using slide media and e-booklets, the results were obtained that there was an increase in the mean value of the pretest to posttest. The results of respondents' pretest knowledge level in the good (20%), sufficient (46%), and less (34%) categories experienced changes in posttest results to good (94%), sufficient (4%), and less (2%). The results of the Wilcoxon statistical test also show that there is an influence of providing menstrual hygiene management education on the knowledge of adolescent girls with p value (0.000) α (0.05). Conclusion: The provision of menstrual hygiene management education effectively increases the knowledge of adolescent girls at SMP N 35 Pekanbaru.